UUM Library Mobile-Based Book Reservation System - Massoud, Wael Ali (2008)
Reserving a book online is the newest facility developed in most libraries all around the world. In reserving books from the library, students have to access the UUM library website. Therefore, students must have a PC, laptop or similar device that can access the Internet. However, not all students have their own PC, laptop or PDA to access the Internet from wherever and whenever they wish. This paper attempts to design a Mobile-based Book Reservation System, as well as a new mobile system that can be used by UUM students to check the availability of books and to make reservation for the required books from wherever they are or whenever they want. UML is used as the modeling language for the design of the system, usability testing is included, system development life cycle is used for planning and analysis of the project and UML approach is used to design the system. The last section highlights few limitations that could be considered for future work.